Realizing Gedangan Village as an energy self-sufficient village through biogas-electric energy conversion - Andi Widiyanto; Bagiyo Condro Purnomo (Community Empowerment, 2021)
Gedangan village, a dairy farming center, has many biogas reactors that are used for cooking and lighting petromax lamps. Previous community service activities resulted in the construction of three Biogas Power Plants (PLT-Biogas) capable of producing 15 kW of power but which were not fully utilized. Participatory Rural Appraisal (PRA) is the approach method used to actively involve the community in the program. To optimize the PLT-Biogas, the service team rearranges the equipment and replaces the UPS with an inverter and battery charger before constructing a street lighting electricity network that can be used by the entire community. The next step is to provide operational and maintenance training for the long-term use of PLT-Biogas. As a result, the initial stage of electrical energy is currently used for street lighting in two hamlets, as well as freezers and water pumps, with a potential savings of 2,775.6 kWh per year. By converting biogas energy to electricity, this community service activity can help to kickstart the realization of an energy self-sufficient village.